The Long Non-coding RNA ZFAS1 Sponges miR-193a-3p to Modulate Hepatoblastoma Growth by Targeting RALY via HGF/c-Met Pathway - Cui, Xichun; Wang, Zhifang; Liu, Liwen; Liu, Xin; Zhang, Dandan; Li, Jianhao; Zhu, Jianming; Pan, Juntao; Zhang, Da; Cui, Guangying (Frontiers in Cell and Developmental Biology, 2019)
Hepatoblastoma (HB) is the most common and aggressive malignant hepatic neoplasm in childhood and the therapeutic outcomes remain undesirable due to its recurrence and metastasis. Recently, long non-coding RNA (lncRNA) zinc finger antisense 1 (ZFAS1) has been reported to be an oncogenic gene in multiple cancers. However, the expression status and specific role of ZFAS1 involved in cancer progression of human HB remain unknown. This study aimed to identify the role of ZFAS1/miR-193a-3p/RALY axis in the development of HB. Here we showed that the expression of ZFAS1 was significantly upregulated in both HB tissues and cell lines. High ZFAS1 expression was significantly associated with aggressive tumor phenotypes and poorer overall survival in HB. In vitro and in vivo function assays indicated that silencing of ZFAS1 significantly suppressed HB cell proliferation and invasion. Furthermore, miR-193a-3p was identified to be the target of ZFAS1. Subsequently, RALY was confirmed to be regulated by miR-193a-3p/ZFAS1 axis. Mechanistically, our results indicated that the ZFAS1 participated to the progression of HB via regulating the HGF/c-Met signaling. Collectively, these data demonstrated that ZFAS1 acted as an oncogene to promote initiation and progression of HB by regulating miR-193a-3p/RALY axis via HGF/c-Met Pathway, which provides an efficient marker and new therapeutic target for HB.